Reception of Translated Classics of Traditional Chinese Medicine in the Spanish-speaking World: A Survey of Seven Spanish Versions of Huangdi Neijing (The Yellow Emperor's Inner Classic) - Wen-Wen Hu (Wolters Kluwer Health/LWW, 2022)
Previous studies on translations of Huangdi Neijing (The Yellow Emperor's Inner Classic) have focused on English versions; little attention has been given to non-English translations. The present study is the first investigation of the reception of the seven Spanish versions of Huangdi Neijing in terms of three parameters: collection records in libraries worldwide; book reviews and citation counts in international journals; and customer reviews on Amazon. The results revealed four features of Spanish translations and communication of Huangdi Neijing in terms of reception of academia, reception of general readers, the center of translation and communication, and the role of Chinese scholars. These factors demonstrate the marginal status of Spanish translations of traditional Chinese medicine (TCM) classics. The implications are summarized in hopes of promoting the translation and communication of TCM classics in the Spanish-speaking world and to provide insights into the communication of TCM culture in the non-English-speaking world.